Effects of different levels of dietary protein on the growth performance, nutrient utilization, digestive enzymes and physiological status of white shrimp, Litopenaeus vannamei juveniles reared in inland saline water. (24th September 2020) - Talukdar, Avinash; Dharmendra Deo, Ashutosh; Prasad Sahu, Narrotam; Sardar, Parimal; Aklakur, Muhammad; Harikrishna, Vungarala; Prakash, Satya; Shamna, Nazeema; Jana, Prasanta
Abstract: A 60‐day feeding trial was conducted to illustrate the effect of dietary protein levels on the growth and physio‐metabolic responses of juvenile Litopenaeus vannamei reared in inland saline water (ISW). Six isoenergetic (15 MJ/kg) and isolipidic (60 g/kg) diets with graded level of crude protein viz., 240 (T240), 260 (T260), 280 (T280), 300 (T300), 320 (T320) and 340 (T340) g/kg diet were formulated. Significantly higher ( p  < .05) weight gain (%), specific growth rate, with lower food conversion ratio were found in T320 and T340 groups. The protein utilizing efficiency and whole‐body protein content were significantly higher ( p  < .05) in the T320 group. Trypsin activity increased with the increasing dietary CP level but amylase activity decreased with the increasing dietary CP level. Transaminase enzymes, haemolymph protein and haemocyanin were elevated in T320 and T340 groups. The lactate dehydrogenase and malate dehydrogenase activities were significantly higher ( p  < .05) in the T240 group. Shrimp of T240 group had the lowest ( p  < .05) glycogen and total haemocyte count with highest ( p  < .05) haemolymph glucose and antioxidant enzymes activities than the other groups. Based on the results, feeding 320 g CP/kg is found to be optimum for supporting maximum growth and health status of L. vannamei reared in ISW at 8 g/L salinity. The finding of the present study will help in developing a low‐cost feed for L. vannamei reared in ISW.